(untitled) (Research, Society and Development, 2023)
In recent years, special attention has been given to minimizing or reusing solid waste generated in different industrial processes. Waste from the food industry involves appreciable amounts of peel, pit and others. These materials, in addition to being a source of organic matter, serve as a source of proteins, enzymes and essential oils, which can be recovered and used. The objective of this work was to evaluate the toxicity of agro-industrial residues from pineapple (Ananas comosus L. Merrill) through a bioassay with Artemia salina. Different concentrations of pineapple residue (0, 200, 400, 600, 800 and 1000 mg.kg-1) were added to the nauplii and the average lethal dose (LD50) was evaluated using Probit analysis using the Bio Stat 2009® software, obtaining the upper and lower confidence intervals after an exposure period of 24 hours. Extracts were considered active when values were < 1000 µg.mL-1. For pineapple residues, the LD50 was 2,215.412 µg.mL-1 for a 95% confidence interval, these residues being considered inactive. It can be concluded that the pineapple residues were non-toxic to Artemia salina in the different concentrations tested.